PENGARUH CURRENT RATIO DAN DEBT TO ASSET RATIO TERHADAP RETURN ON EQUITY PADA PT UNILEVER INDONESIA TBK PERIODE 2013-2023 - Submission JORAPI; Laraswati Safitri; Siti Nurcahayati (Journal of Research and Publication Innovation, 2025)
The purpose of this research is to determine the influence of the current ratio and debt to asset ratio on return on equity at PT Unilever Indonesia Tbk for the 2013-2023 period. The independent variables in this research are the Current Ratio and Debt to Asset Ratio and the dependent variable used is Return On Equity. This sample and population collection was carried out by taking 11 years of data from the period 2013 to 2023. The method used in this research is descriptive quantitative with the help of SPSS Statistics Version 29. The results of the research show that the Current Ratio data partially has no effect on the Return On Equity variable. . This is proven by the t count which is smaller than the t table (0.755 < 2.306) and the sig value is greater than the significance level (0.472 > 0.05). However, Debt To Asset Ratio data partially influences Return On Equity. This is proven by the calculated t which is greater than the t table (2.607 > 2.306) and the sig value is smaller than the significance level (0.031 < 0.05). Current Ratio and Debt To Asset Ratio simultaneously influence the dependent variable on Return On Equity at PT Unilever Indonesia Tbk with a calculated F value of 9,141 > 4.46 and a significance level of 0.009 which is smaller than 0.05. And the influence of the independent variables (Current Ratio and Debt To Asset Ratio) on Return On Equity is 0.620 or 62.0%, while the remaining 38.0% is influenced or explained by other variables not included in this research model.